Contextualizing Overdoses in Los Angeles's Skid Row between 2014 and 2016 by Leveraging the Spatial Knowledge of the Marginalized as a Resource. Issue 6 (2nd November 2018) - Curtis, Andrew; Felix, Chaz; Mitchell, Susanne; Ajayakumar, Jayakrishnan; Kerndt, Peter R.
Abstract : Opioid drug overdoses in the United States have continued to rise since 2014. Overdoses are one of several interlinked health challenges faced by marginalized populations. Here we side with the argument that these populations can also be a valuable resource to address these challenges, and we use methods that can elevate this critical belief into real-world application. In this article, we use spatially inspired interviews from both marginalized and provider participants in the Los Angeles Skid Row to map out the microspaces of drug activity. The resulting map reveals a complex space in terms of drug types and associated social activities. These geonarratives reveal a nuanced space of locations, activities, and context—how these substances enter Skid Row, the associated violence, and the physical and emotional toll on the marginalized. We find both quantitative and qualitative support that the "street" community is complex, full of variation in terms of where people live, how they live, and the social fabric that has evolved. We suggest that these data can be used to reduce the structural violence often found in many "solutions" to the homeless and their problems. Instead we show that the marginalized could be used to provide a vital resource not only in terms of their knowledge and their communities but also in delivering medical care. We end by suggesting that this approach to data collection could evolve into an ongoing resource that could develop into a near-real-time tool to reduce overdose mortalities. Key Words: geonarrative, GIS, marginalized, overdose, Skid Row .